2011
DOI: 10.1002/jgm.1531
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of CTLA4Ig gene‐transduced adipose tissue‐derived mesenchymal stem cells reduces inflammatory immune response and improves Th1/Th2 balance in experimental autoimmune thyroiditis

Abstract: Although CTLA4Ig-MSC transplantation had better result in reduction of serum TgAA, both of ATMSC and CTLA4Ig-MSC transplantations are promising treatments for autoimmune thyroiditis judging from the results of histopathology and cytokine analysis. They may be attractive candidates for treating organ-specific autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 32 publications
4
51
0
Order By: Relevance
“…In this study, we see significant suppression of IFNg when MSCs expressing CTLA4Ig are cultured with T cells at both 24 and 72 h. This reflects the known effects of MSCs on suppressing IFNg production and the reported reduction in systemic IFNg post-CTLA4Ig therapy in RA patients [52]. It is also known that MSCs expressing CTLA4Ig may be used to alter the Th1:Th2 cytokine profile to favour Th2 cytokine production and ameliorate experimental autoimmune thyroiditis [34]. It is likely that MSCs and CTLA4Ig act syngertistically to alter suppress T cell activation, reduce production of IFNg and cause a shift towards a Th2 cytokine response in inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this study, we see significant suppression of IFNg when MSCs expressing CTLA4Ig are cultured with T cells at both 24 and 72 h. This reflects the known effects of MSCs on suppressing IFNg production and the reported reduction in systemic IFNg post-CTLA4Ig therapy in RA patients [52]. It is also known that MSCs expressing CTLA4Ig may be used to alter the Th1:Th2 cytokine profile to favour Th2 cytokine production and ameliorate experimental autoimmune thyroiditis [34]. It is likely that MSCs and CTLA4Ig act syngertistically to alter suppress T cell activation, reduce production of IFNg and cause a shift towards a Th2 cytokine response in inflammatory arthritis.…”
Section: Discussionsupporting
confidence: 66%
“…The use of allogeneic cells would increase the potential use of this therapy and therefore, the use of MHC mismatched MSCs [18] was used to determine migration to the joint in vivo and the impact of allogeneic MSCs secreting CTLA4Ig on disease progression in CIA in DBA/1 mice. CTLA4Ig is currently licensed for clinical use in RA and MSCs expressing CTLA4Ig have been shown to be of therapeutic benefit in animal models of graft versus host disease [33] and autoimmune thyroiditis [34]. The cotransfection of MSCs may also be used to facilitate other gene therapy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…the ability of haDSCs to downregulate th1 cytokines has been recently demonstrated in experimental autoimmune thyroiditis. 5 Systemic infusion of haDSCs prevents lymphocyte infiltration to thyroid glands, decreases the production of pro-inflammatory cytokines and improves the th1/th2 balance. Similar to MSCs, haDSCs can suppress t-cell proliferation and cytokine production in response to alloantigens and non-specific antigens and can inhibit the function of B-, natural killer-and dendritic cells.…”
Section: Merging Innovations To Advance Stem Cell Research and Therapiesmentioning
confidence: 99%
“…Recent studies on successful MSC treatment in autoimmune diseases have been reported. Further, in our previous studies on autoimmune thyroiditis and rheumatoid arthritis, CTLA4Ig-ASCs showed stronger suppression in the T cell proliferation against autoantigens and were more effective in reducing serum levels of autoantibodies than non-transduced ASCs were [17][18][19].…”
Section: Introductionmentioning
confidence: 99%